Imaging modalities for drug-related osteonecrosis of the jaw (3), Positron emission tomography imaging for the diagnosis of medication-related osteonecrosis of the jaw. Issue 1 (November 2019) - Kitagawa, Yoshimasa; Ohga, Noritaka; Asaka, Takuya; Sato, Jun; Hata, Hironobu; Helman, Joseph; Tsuboi, Kanako; Amizuka, Norio; Kuge, Yuji; Shiga, Tohru
Summary: Medication-related osteonecrosis of jaws (MRONJ) is one of the most complicated inflammatory conditions in oral and maxillofacial region. It is very difficult to correctly evaluate the degree and extent of necrosis and infection. This refractory osteonecrosis often needs extended surgery, leading to impaired quality-of-life. We have performed hyperbaric oxygen therapy (HBO) combined with conservative surgery for advanced cases. We have appraised the value of FDG-PET and 3-phase bone scintigraphy in the diagnosis and management of this condition. MRONJ showed significantly higher SUVmax on FDG-PET than the others. Although the 3 phase pool bone images did not change significantly, perfusion and static bone image as well as PET showed remarkable response to HBO for MRONJ. SUVmax after HBO was significantly lower than those of before HBO. These preliminary results indicate that FDG-PET is useful for monitoring the effect of HBO for MRONJ.